Copolymerization of 4-methyl-1-pentene with α,ω-alkenols - W. Wang; L. Hou; J. Sheng; M. Ren; Y. Tang (eXPRESS Polymer Letters)
Copolymerization of 4-methyl-1-pentene (4M1P) with 9-decen-1-ol (9D1O) or 4-penten-1-ol (4P1O) was conducted by using metallocene catalysts. The activity could be improved under the higher polymerization temperature. The dyad distribution of poly(4M1P-co-4P1O) was presented. The results showed that 4P1O was uniformly distributed in the copolymer chain. The melting temperature (Tm) of the copolymer was lower than that of poly(4M1P), and was decreased with the increase of the incorporation of comonomer. Tm of poly(4M1P-co-4P1O) was determined as 185 °C, even the incorporation of 4P1O was high as 15.0 mol%. WAXD (wide-angle X-ray diffraction) results showed that the poly(4M1P) was observed as crystalline form II, and turned to form I when the incorporation of α,ω-alkenols were high. Some new peaks, which were never observed in the previous researches, appeared in the X-ray diffraction profiles for poly(4M1P-co-4P1O). It is inferred that the similar chain length of 4P1O and 4M1P may be the key factor.